Thermal management for smart windows with magnetic induced actuation - Ng, Rayner Bao Feng (Nanyang Technological University, 2021)
To achieve carbon neutrality in the global building sector, heavy emphasis has been placed on developing smart window technologies to reduce cooling and heating loads, and consequently reduce energy consumption which is primarily supplied by fossil fuels. Currently, most development of smart windows focuses primarily on chromogenic technologies that regulate solar heat gain. However, a major drawback of such solutions is the lack of night-time operations. Hence, there is an opportunity to develop other types of smart windows based on thermal conduction allowing for both day and night operation. Here, the thermal transmittance regulation of a double-glazed window is reported. A magnetically actuated thermal bridging switch device was fabricated and tested both experimentally and by finite element analysis. The prototype device demonstrated a reversible 20% difference in thermal transmittance. This led to a decrease in building energy consumption as evaluated by EnergyPlus simulations, suggesting an interesting area of research for smart windows with variable thermal transmittance.